The impact of structural complexity on knowledge management processes: a case study of the friendship Ophthalmology Hospital Algeria Cuba in DJELFA - Mokhtar Rabhi; Ahlam Thamri; Mohammed Said Djoua; Rima Affaf Harizi; Souaad Ben Messaoud (Revista Cubana de Administración Pública y Empresarial)
The hospital is a complex system that includes several variables, and knowledge represents the most critical input that interacts in order to effectively meet patients' needs. The study sought to empirically test the relationship between structural complexity and its dimensions: horizontal differentiation, spatial differentiation, vertical differentiation and knowledge management processes: acquisition, storage, distribution, and application among a sample of workers at the Friendship Ophthalmology Hospital Algeria Cuba in Djelfa. A questionnaire was designed to collect data from the study sample, and the data was processed and analyzed based on the SPSS 22 and Smart Pls 4 programs. The study yielded results, the most important of which are: There is a significant effect of horizontal and spatial differentiation on Knowledge management processes in the hospital. The study recommends adopting information and communication technology and integrating it into various hospital operations to simplify healthcare practitioners' tasks.